Sustaining Taudaha: The Role of Ecotourism in Conservation and Development (The Himalayan Geographers, 2025)
The contribution of ecotourism to the sustainable development in Taudaha is the main aim of this study. It is a tiny wetland in a Kathmandu suburb that is significant both culturally and ecologically. In order to assess the economic, ecological, and social effects of ecotourism, the study used a mixed-methods approach that includes surveys, interviews, focus group discussions, and field observations. The findings support a number of Sustainable Development Goals (SDGs) by demonstrating that ecotourism plays a vital part in the local livelihoods, infrastructural development, and environmental awareness. The biodiversity of Taudaha, especially the wetland bird species, is a major drawback to its ecotourism promotion. Similarly, the issues of poor waste management, less community participation, and commercialization risks endure, challenging the area. Therefore, the research proposed co-operation among stakeholders and community-based methods as ways to guarantee equal sharing of benefits and protection of the ecology and environment. Thus, uncovering the potential of ecotourism as a model for integrated development.